2021
DOI: 10.1177/00220345211003490
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 as a Regulator of Aquaporin 5 Expression in the Salivary Gland

Abstract: Forkhead box O1 (FoxO1) is a multifunctional initiator, mediator, and repressor of autoimmune diseases in an organ- or disease-specific manner. However, the role of FoxO1 in the salivary gland has not yet been elucidated. In this study, we discovered that FoxO1 and aquaporin 5 (AQP5) are both significantly downregulated in the patients with primary Sjögren syndrome, an autoimmune disease accompanying salivary gland dysfunction. Pharmacologic or genetic perturbation of FoxO1 in the rat salivary gland acinar cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…AQP5 is embedded in the lipid bilayer of the cytoplasmic membrane and forms a tetramer. Due to the unique structure of AQP5, it plays an important role in the transmembrane transport of water and small molecular compounds [ 28 ]. Previous studies have reported that AQP5 cooperates with the calcium channel TRPV4 to regulate cell volume [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…AQP5 is embedded in the lipid bilayer of the cytoplasmic membrane and forms a tetramer. Due to the unique structure of AQP5, it plays an important role in the transmembrane transport of water and small molecular compounds [ 28 ]. Previous studies have reported that AQP5 cooperates with the calcium channel TRPV4 to regulate cell volume [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that FOXO1 directly regulates AQP5 expression in salivary gland acinar cells. FOXO1 is a direct regulator of AQP5 expression in salivary gland acinar cells through its interaction with the promoter region of AQP5 [69]. AQP5 is the most important protein for salivation since it directly mediates the transcellular movement of water from the basal to apical or lumen side of acinar cells [70].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the only data on aquaporins and the FOXO family were obtained on salivary gland cells where AQP5 was found to be regulated by FOXO1 [147]. However, in breast cancer the FOXO family is down-regulated, while AQP5 is up-regulated and positively correlated with its malignancy [30,54,148].…”
Section: Foxomentioning
confidence: 99%